The Analysis Of Gastrointestinal Symptoms Impacted By Whole Body Vibrations On Workers Of Deliveryman And Helper With Age 40 Years PT. Coca Cola Amatil Indonesia - Samion, Marzuki (Jurnal Teknik Informatika UNIKA Santo Thomas, 2018)
The study of whole body vibration has been widely applied in various industries by demonstrating the various impacts and complaints. The objective of this research is to analyze the study of gastrointestinal symptoms, dyspeptic derived from whole body vibration deliveryman workers and helpers within distribution vehicles due to engine vibration transmitted through the vehicle seat. The design of the study was using cross-sectional design. The sampling technique used purposive sampling; as many as 60 workers were aged less than 40 years from a total of 75 workers in the field of distribution for North Medan operational areas, and focused on the 30 distribution trucks. To analyze the gastrointestinal symptoms of dyspeptic due to the effects of whole body vibration that was affecting to the workers, electrically analysis with IBM SPSS software version 20. The results that vibration which exposes to helper seat to reach average of 7.15 m/s 2 and deliveryman seat reach average to 6.68 m/s 2 . According to the standard comfortable reaction, the result that obtained can cause a reaction that is very uncomfortable for the workers. The amount of exposure received helper due to engine vibration propagation directly received through a seat before it spread to the seat of deliveryman. A total of 12 people from the deliveryman and 9 helper suffered of dyspeptic symptoms and dyspeptic symptoms based on the statistics that come from whole body vibration of workers due to machine vibration of distribution trucks. This condition is seen from the results of chi-square calculation on each group of workers, which shows the chisquare test> tables and chi-square probability